The PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION PADA SOCIAL BELLA (SOCIOLLA): THE EFFECT OF RELATIONSHIP MARKETING ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION IN SOCIAL BELLA (SOCIOLLA) - Valentia Dian Arsanti; Kristina Sisilia (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to understand the effect of relationship marketing on customer loyalty through customer satisfaction as an intermediary variable in the Social Bella Indonesia business, or known as the Sociolla brand, as e-commerce and has a well-known onsite store in the beauty industry. Consumers choose to always shop loyally at Sociolla because of the various relationship models built and provided by Sociolla to ensure product information can be accessed at competitive prices so that consumers are satisfied in their shopping experience and always purchase various beauty products only at the Sociolla store. This research uses quantitative methods with a purposive sampling technique on 100 consumers who subscribe to shopping at Sociolla stores and applies path analysis. The analysis results show a positive and significant influence between relationship marketing on customer satisfaction of 76,9%, a significant positive effect of relationship marketing on customer loyalty of 8,9% and finally, a positive and significant influence between customer satisfaction on customer loyalty of 32,2%. Sociolla and similar businesses can use the findings in this research to execute only relationship marketing activities that impact customer satisfaction so that consumers will always repeat orders and upsell for purchases in the future.